The in-silico study of the structural changes in the Arthrobacter globiformis choline oxidase induced by high temperature - Sonia Kaushik; Rashmi Rameshwari; Shilpa S. Chapadgaonkar (Journal of Genetic Engineering and Biotechnology, 2024)
Background: Choline oxidase, a flavoprotein, is an enzyme that catalyzes the reaction which converts choline into glycine betaine. Choline oxidase started its journey way back in 1933. However, the impact of the high temperature on its structure has not been explored despite the long history and availability of its crystal structure. Both choline oxidase and its product, glycine betaine, have enormous applications spanning across multiple industries. Understanding how the 3D structure of the enzyme will change with the temperature change can open new ways to make it more stable and useful for industry. Process: This research paper presents the in-silico study and analysis of the structural changes of A. globiformis choline oxidase at temperatures from 25 °C to 60 °C. A step-wise process is depicted in Fig. 1. Results: Multiple sequence alignment (MSA) of 11 choline oxidase sequences from different bacteria vs Arthrobacter globiformis choline oxidase showed that active site residues are highly conserved.The available crystal structure of A. globiformis choline oxidase with cofactor Flavin Adenine Dinucleotide (FAD) in the dimeric state (PDB ID: 4MJW)1 was considered for molecular dynamics simulations. A simulated annealing option was used to gradually increase the temperature of the system from 25 °C to 60 °C. Analysis of the conserved residues, as well as residues involved in Flavin Adenine Dinucleotide (FAD) binding, substrate binding, substate gating, and dimer formationwas done. At high temperatures, the formation of the inter-chain salt bridge between Arg50 and Glu63 was a significant observation near the active site of choline oxidase. Conclusion: Molecular dynamics studies suggest that an increase in temperature has a significant impact on the extended Flavin Adenine Dinucleotide (FAD) binding region. These changes interfere with the entry of substrate to the active site of the enzyme and make the enzyme inactive.